STUDY OF PLASMODIUM FALCIPARUM 3D7 INHIBITOR ACTIVITY OF KAYU KUNING - Sulistiarini, Riski
Indonesian government still has a big challange to do for 10.7 million people living in endemic areas to be free of malaria to achieve malaria-free Indonesia in 2020. The biggest challenge in is the occurrence of parasitic resistance to antimalaria drugs and vector resistance to insecticides. The development of antimalarial drugs is still very minimal, although many plants have been used ethnopharmacologically to treat malaria. They also have been tested in laboratories that meet the requirements, but the development of new antimalarial drugs from natural products is interfered by the lack of understanding in the mechanism of action of these compounds or natural ingredients. Kayu kuning, an endemic plant in East Kalimantan, is a common name used for Archangelisi flava, Fibraurea tinctoria, and Coscinium fenetratum. Genetic identification of the kayu kuning has been carried out to identify the species of kayu kuning that is empirically used as antimalaria in Kalimantan. The result reported that the species is A. flava, with the index similarity of nucleotide of 94.16% compared to the Genbank database. The extraction process was carried out on three species of kayu kuning and the yields of methanolic extract of A. flava, F. tinctoria , and C. fenstratum were 5.22%, 5.5%, and 8.07%, respectively. All extracts were tested in vitro for antimalarial activity based on growth inhibition of Plasmodium falciparum 3D7 cells. Observation was carried out microscopically in 10,000 erythrocytes. The result showed the IC50 value for methanolic extracts of A. flava, F. tinctoria and C. fenestratum were 0.57, 0.08 and 0.09 µg/mL, respectively. F. tinctoria had the best vi inhibitory activity against Plasmodium falciparum and was chosen for further investigation. F. tinctoria extract was then fractionated by the solvent extraction method using organic solvents with increasing polarity. The yield value for n-hexane, ethyl acetate, and water-methanol fraction were 1.94%, 1.94%, and 45.48%, respectively. Each fraction was identified by its berberine content, and this guided further purification process. Furthermore, identification of the berberine content of each fraction is carried out because the yellow wood plant contains the major compound berberine. Regulation of the Food and Drug Supervisory Indonesia Number 10 of 2014 lists berberine as one of the prohibited ingredients contained in traditional medicines and health supplements. Identification was carried out using TLC and HPLC methods. The identification results showed that there were stains that were seen parallel from the ethyl acetate fraction and the water-methanol fraction with the stains from berberine. HPLC results showed that the fraction of n-hexane, ethyl acetate and water-methanol fraction contained berberine with levels of 0.0010%; 0.0041% and 0.0044%. From the identification results, the n-hexane fraction was continued at the next testing stage because it contained the smallest amount of berberine among the other fractions. The next step was the sub-fractionation of n-hexan fractions by column chromatography using n-hexane and ethyl acetate as the eluent in different ratio with increasing polarity. The sub-fractionation resulted in eight n-hexane subfractions, identified as HA, HB, HC, HD, HE, HF, HG, HH. Subfraction was tested against P. falciparum 3D7 using the pLDH Assay method. Observations were made on cultures with the formazan blue color reaction. The test results showed that HH subfraction showed a very active inhibition (IC50 <1 µg / mL) with an IC50 value of 0.43 µg / mL, HB, HC and HE subfraction had the inhibitory ability with the active category (1 µg / mL <IC50 <5 µg / mL) with IC50 values of 2.89, respectively; 6.16; and 2.29 µg / mL while the other subfractions showed no inhibitory activity. Of all n-hexane subfractions, HB subfraction shows the IC50 value with the category of active inhibition and a sufficient amount of subfraction gain. Upon furtherr purification and structural elucidation, it was revealed that the isolate was comprised of ?-sitosterol and stigmasterol compounds. This isolate was then tested for inhibitory activity against P. falciparum 3D7 by the pLHD Assay method, which revealed in an IC50 value of 4.15 µg / mL (active). HB isolate was further tested for its mechanism of action on P. falciparum Dihydroorotate Dehydrogenase (PfDHODH) and P. falciparum Malate Quinin Oxydoreductase (PfMQO) enzymes which play a critical roles in electron transport and glycosylation. It was found that HB isolate inhibited the PfMQO enzyme of P. falciparum with an IC50 value of 418.72 µg/mL. This activity resulted in the inhibition of electron transport in the mitochondria and gave an antimalarial effect.